2017
DOI: 10.5114/aoms.2017.65239
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibitors – from discovery of a single mutation to a groundbreaking therapy of lipid disorders in one decade

Abstract: Hypercholesterolemia is one of the main risk factors for coronary heart disease and significantly contributes to the high mortality associated with cardiovascular diseases. Statin therapy represents the gold standard in the reduction of low-density lipoprotein cholesterol concentration. Nevertheless, many patients still cannot achieve the recommended target levels, due to either inadequate effectiveness or intolerance of these drugs. Monoclonal antibodies that inhibit proprotein convertase subtilisin/kexin typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 111 publications
(118 reference statements)
0
16
0
Order By: Relevance
“…The inhibition of PCSK9 (protein convertase subtilisin/kexin 9) is an efficient strategy for lowering cholesterol and low-density lipoprotein cholesterol (LDL-C) [32]. In a study by Momtazi-Borojeni et al, the anti-PCSK9 antibody was induced via a vaccine in mice inoculated with breast carcinoma cells.…”
Section: Cholesterol and Breast Cancer In Animal Studiesmentioning
confidence: 99%
“…The inhibition of PCSK9 (protein convertase subtilisin/kexin 9) is an efficient strategy for lowering cholesterol and low-density lipoprotein cholesterol (LDL-C) [32]. In a study by Momtazi-Borojeni et al, the anti-PCSK9 antibody was induced via a vaccine in mice inoculated with breast carcinoma cells.…”
Section: Cholesterol and Breast Cancer In Animal Studiesmentioning
confidence: 99%
“…Consequently, there are not enough LDLRs to remove plasma LDL-C when the circulating level of PCSK9 is increased as a result of gain-of-function mutations [15], whereas low levels of plasma PCSK9, due to loss-of function mutations, will lead to more intact LDLRs which in turn take up more plasma LDL-C [15]. Therefore, PCSK9 inhibition has emerged as a therapeutic tool and is currently used as an effective LDL-lowering approach in hypercholesterolemic patients [16][17][18][19][20][21][22][23]. Although the safety of PCSK9 inhibitors in hypercholesterolemic conditions has been approved, there is scant information on the safety of PCSK9 inhibition in other conditions such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have shown that gain-of-function mutations in PCSK9 were causatively associated with increased plasma levels of LDL-C [19], while loss-of-function mutations were associated with hypocholesterolemia and a reduced risk of coronary artery disease [20][21][22]. This association has also been confirmed in proof-of-concept clinical trials [23][24][25][26][27][28][29][30]. Of note, it was recently reported that LDL-raising genetic variants of PCSK9 were associated with a higher risk of breast cancer, while LDL-lowering variants mimicking PCSK9 inhibitors were found to have significant association with a lower risk of breast cancer occurrence [16].…”
Section: Introductionmentioning
confidence: 88%